QUANTITATIVE ASSESSMENT OF ACADEMIC DISCIPLINE PREPARATION - Oleg A. Polushkin; Georgy I. Kanygin; Maria O. Polushkina (Advanced Engineering Research, 2011)
Original quantitative assessment of the qualitative academic discipline preparation has been worked out. It considers all the factors which define this quality, and describes one of the characteristics of the developed functional model of this discipline preparation.